Faktor-Faktor Yang Berhubungan Dengan Siklus Menstruasi Pada Remaja Putri Kelas XI di SMA Negeri 6 Tangerang Selatan - Ayatun Fil Ilmi; Elyn Widya Selasmi (Edu Masda Journal, 2019)
Menstruation is the release of blood and the rest of the endometrium from the vagina. The first day of menstruation is considered to be the beginning of a new cycle. Menstrual cycle is the distance between the date of the start of a previous menstruation and the onset of menstruation. Irregular menstrual cycles can be received by infertility, 28% Increased risk of coronary heart disease, and type 2 diabetes mellitus. The aim of this study is to study the factors related to the menstrual cycle in adolescent girls in South Tangerang City Senior High School 6. Study design: in this study was cross sectional with sampling using the simple random sampling method. The study sample returned 64 people from the XI class of SMA Negeri 6 South Tangerang City. The variables that are issued are nutritional status, stress level, physical activity, and age of menarche. Data about the menstrual cycle, stress level, physical activity obtained by temporary interviews of the Body Mass Index by measuring body weight and height. Data processing is done by chi square test analysis. Results: Research shows as many as 59.4% of respondents who experience irregular menstrual cycles. There was a significant relationship between menarche age (p = 0.028) with the menstrual cycle. And balanced nutritional status (63.2%) to have irregular menstrual cycles. Conclusion: From the results of the analysis of the data it can be concluded that there is a relationship between the age of menarche and the menstrual cycle. And there is no relationship between nutritional status (p = 0.822) with the menstrual cycle.